Cacophony and Harmony: The Contrapuntal Voices of Indian Diasporic Literature - Rajeswaran, Sivanesan (Journal of Research in Vocational Education, 2026)
There is a cacophony and harmony in diasporic literature as a result of the dichotomous nature of voices stemming out of the diversity of experiences of diasporic writers. Diasporic writers are diverse in that they have different levels of experience as well as acceptability in their host countries. India is a diverse culture in itself. Therefore, the diversity of experience starts at home before one is a diasporic writer. The number of years one has spent in the diaspora as well as the level of sentimental attachment they had toward their home is another factor. In any case, a diaspora literature can have a valuable impact on the home and diaspora Indian audiences provided that the writers have a strong level of commitment toward their home land and a sense of belongingness toward their original culture. This article analyses the diverse dichotomy of voices in diasporic literature. It looks at the contribution that diasporic literature has and the difference it can make in the lives of Indians in modern times.